A Preliminary Investigation of the Effect of Protective Clothing Weight, Bulk and Stiffness on Combat Mobility Course Performance. (September 2016) - Bossi, Linda L.M.; Jones, Monica L.H.; Kelly, Alison; Tack, David W.
Soldier loads continue to rise in response to new technological capabilities and emerging threats. However, literature addressing the extent to which load mass properties affects operational task performance and mission outcome is sparse. The objective of this preliminary study was to quantify the effect of PPE mass properties (weight, bulk and stiffness) on combat mobility, as measured using the standardized Load Effects Assessment Program (LEAP) course. Twenty-four soldiers completed the LEAP course in three clothing and individual equipment (CIE) configurations (UE: unencumbered; FFO: full fighting order (FFO) without body armour; and FFO+: FFO with body armour). Significant differences between clothing conditions were revealed for LEAP performance metrics (overall course time). Regression analysis revealed significant relationships between overall mobility performance and condition mass properties of weight, bulk, and stiffness. Outcomes will influence the design of future CIE and future research in this area.